Worry, Boredom, and Embarrassment GXNU Chinese Students' Emotions in BIPA Learning at Universitas Negeri Malang - Iwa Sobara; Didan Nurfadillah; Savira Putri Destiani; Regina Nadya Gading Kurniawan (Nexus Publishing NXP, 2026)
Foreign language learning involves not only linguistic competence but also emotional factors that influence learning effectiveness. This study explores the emotional experiences of Guangxi Normal University (GXNU) students in the 3+1 program at Universitas Negeri Malang (UM) during BIPA (Indonesian for Foreign Speakers) learning. Using a descriptive qualitative approach, data were collected through questionnaires and writing tasks from 17 students (13 female, 4 male). The findings indicate that most students experienced positive emotions, with 64.7% reporting no anxiety and a low average boredom score (1.35). Nevertheless, 5.9% still felt anxious, particularly during examinations and academic tasks, while boredom occasionally emerged when learning activities became repetitive. Although emotions such as worry, boredom, and embarrassment are natural in language learning, they may hinder progress if not properly managed. Conversely, moderate anxiety can function as a learning motivator. Therefore, BIPA instructors should adopt emotionally supportive teaching strategies, including scaffolded speaking, pair and group work, context-based tasks, roleplays, and interactive media. These findings align with Sobara et al. (2024), which reported high student satisfaction with teaching methods, learning materials, teacher–student interaction, and the supportive learning environment, indicating the effectiveness of the UM 3+1 BIPA program.